Rational Mindset In The Perspective Of Hadith and Its Implications For The Use Of Social Media - Anggun Puspita Ningrum; Aida Lestari; Fariz Abdillah (Al-Shamela : Journal of Quranic and Hadith Studies, 2024)
This article focuses on discussing the rational mindset taught by the Prophet and its implications for the use of social media. The emphasis on the implications of the Prophet's hadith aims to ensure that in using social media, people are not separated from Islamic norms or teachings, especially in adopting news circulating on social media. In the process, this article uses a qualitative method based on literature data with content analysis. In addition, this article makes the Prophetic traditions that talk about rational thinking as the primary reference and takes some other references, such as verses of the Qur'an as a reference to strengthen the meaning of the hadith presented. Thus, this article concludes that the Prophet has encouraged his people to maximize their intelligence. Rational mindset becomes the main footing in navigating life based on the coffers of Islamic teachings. The implication of the rational mindset taught by the Prophet teaches Muslims that giving news or information must be in accordance with the truth or what it is. All information must be addressed critically by tabayyun, not slandering each other, being polite in communication, using good language, not blaspheming or defaming that can cause hatred.